Integrated assessment results depend on aggregation method and framework structure – A case study within the European Marine Strategy Framework Directive. (February 2016) - Probst, W. Nikolaus; Lynam, Christopher P.
Highlights: Single indicator assessments were aggregated by five different methods. The aggregated assessment results were compared between methods. The applied method influenced the aggregated assessment result. Aggregation results were also dependent on the number of aggregated elements. New aggregation methods were developed to avoid this drawback. Abstract: The ecosystem approach (EA) to environmental management is commonly associated with the holistic, integrative assessment of ecosystem status, where assessments of single elements are aggregated across one or multiple levels. Such an integrative assessment is required by the European Marine Strategy Framework Directive (MSFD). Member states of the European Union must assess the environmental status of their marine waters every six years. For this purpose the MSFD is structured into eleven descriptors of good environmental status (GES), which in turn are subdivided into 29 criteria containing a total of 56 different ecosystem indicators. These 56 indicators are recommended to be used by the member states to assess the status of biodiversity, invasive species, exploited fisheries resources, food webs, seafloor integrity, hydrological conditions as well as the impacts of eutrophication, contamination, litter and anthropogenic noise. The nested structure of the indicators within the commission decision on criteria for GES provides a hierarchy of information, for which aggregation at different levels may be necessary, namely within criteria, within descriptors and across descriptors. However, to date no aggregation rules have been provided by the European Commission. This study explores the implications of five commonly used aggregation methods, once applied with the assessment structure outlined for the MSFD, on the aggregated assessment outcomes at the level of criteria, descriptors and overall GES. Assessing the 56 indicators within the nested structure of the MSFD led to different outcomes between the different methods. Furthermore, all five methods were sensitive to the number of aggregated elements, with higher numbers of assessed elements being associated with lower probability of reaching GES. To overcome this drawback, two new aggregation methods were developed with the aim to ensure that the probability of achieving GES was equal for each indicator, criteria, descriptor and the overall environmental status. This aim was termed as principal of equal probability (PEP). In practice, only one out of the two aggregation methods developed succeeded in maintaining PEP across all hierarchical levels. Whether PEP is imperative for multi-element ecosystem assessments remains to be debated, however, both scientists and managers should be aware of PEP and the implications of its violation.